Deglutition manifestations in patients with oropharyngeal cancer subjected to conservative therapy: systematic review - Jucimara N. Gois; Susana A. Barbosa; Felipe R. Matos; Carla H. Cesar; Luiz Renato Paranhos (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Objectives: To characterize scientific production and identify deglutition changes in individuals with oropharyngeal cancer subjected to conservative therapy. Methods: The search was applied to five electronic database [Scientific Electronic Library Online (Scielo), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), US National Library of Medicine National Institutes of Health (PubMed), Web of Science, and Scopus], besides the search of grey literature in the databases (OpenThesis e OpenGrey), avoiding selection and publication bias. Prospective longitudinal studies concerning the theme: deglutition disorders in individuals with oropharyngeal cancer subjected to conservative therapy were considered eligible. The risk of bias and the evaluation of individual methodological quality of the selected studies were measured by "The Joanna Briggs Institute Critical Appraisal tools for use in JBI Systematic Reviews" for prospective and longitudinal studies. Results: The search resulted in 899 records and after analysis four of them fulfilled the eligibility criteria. Among the studies included, all individuals presented some type of deglutition changes, the most common were: reduced of strength and retraction of the base of the tongue, delayed deglutition trigger, reduced laryngeal elevation, presence of residues on tongue and palate, in the pharyngeal area, valleculae, and posterior pharyngeal wall, as well as in the vestibules and in pyriform sinuses. Conclusion: The evidence from this systematic review suggests that conservative therapies cause deglutition changes or amplify the pre-existing ones, regardless of the type and magnitude of radiation, as well as tumor staging. However, there is little standardization in the research methodologies, making a meta-analysis study difficult to conduct.